Ensuring thermal comfort in the cabin of an electric vehicle at extremely low atmospheric temperatures (down to -45°C) - Alexey V. Shvetsov; Svetlana V. Shvetsova (PLoS ONE, 2025)
Ensuring thermal comfort for the driver and passengers in vehicles, including electric vehicles, when traveling on intercity roads, in sparsely populated northern regions with low traffic, in winter, at extremely low atmospheric temperatures is a critical factor. In this paper, we propose a method of providing additional or alternative heat to the cabin of an electric car, at atmospheric temperatures up to −45°C. To implement this method we developed, a backup electric heater for the cabin of an electric vehicle, which can provide autonomous heat generation for heating people in the cabin, even if the EV itself is completely inoperable. The backup heater is designed to use lithium-iron-phosphate batteries in its structure, which are safer than lithium-ion batteries. An experiment was conducted, as a result of which data were obtained on the discharge rate of the backup heater batteries when operating in three different air temperature ranges (from −20°C to −25°C, from −30°C to −35°C and from −40°C to −45°C) and the temperatures level reached in different parts of the EV cabin. Next, we compared the developed method with other known solutions and analyzed possible applications the backup heater.